Anthropometry for design of filipino child minding center in Davao City - Bonghanoy, Vanessa B.; Orendain, Dan Jezreel A. (2015)
Child care services are important for the young children and their families. Establishing a child care center committed to the support of these services enables children to be successful in school and in life. This can only be possible if there is a development and availability of high quality child care where all children can thrive in supportive, nurturing and loving environment. Using Qualitative Research, the researcher was able to gain a holistic (systematic, encompassing, integrated) overview of the context under study. The data was strengthened through descriptive numerical measures and inferential statistics from interviews and surveys. The Anthropometry for Design of Filipino Child Minding Center in Davao City ensures Filipino families that not only the best care, attention, and early learning simulation will be given to their child but also an efficient learning environment for the whole facility itself.
Thesis (BS Architecture) -- University of the Philippines Mindanao, 2015